2019
DOI: 10.2478/limre-2019-0005
|View full text |Cite
|
Sign up to set email alerts
|

Ice cover thickness formulas for selected flow-through lakes of the upper Łeba River (Kashubian Lakeland, northern Poland) and an overview of GIS methods, models for determining the thickness of ice cover on the selected examples

Abstract: The lakes selected for the analysis are situated in the Kashubian Lakeland which is a proper research area as there is a benchmark lake with a long data series within the region. This lake is located in the central part of the lakeland, in the upper Radunia water catchment area, while the lakes not being hydrometrically supervised constitute part of the upper Łeba water catchment area. The main objective of this study is to determine the relationship between ice cover thickness on the flow-through lake undergo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…As Choiński et al (2015) have shown, a weaker strength of connection, except a local temperature variation, might be responsible for the individual morphometric features (lake volume and depth) of individual lakes. The results were even better for the models concerning the selected lakes of the upper Łeba River (Barańczuk 2019). In this case, the strength of relationship varied from good to very good with R 2 = 0.881 for Lake Łapalickie and 0.929 for Lake Reskowskie.…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations
“…As Choiński et al (2015) have shown, a weaker strength of connection, except a local temperature variation, might be responsible for the individual morphometric features (lake volume and depth) of individual lakes. The results were even better for the models concerning the selected lakes of the upper Łeba River (Barańczuk 2019). In this case, the strength of relationship varied from good to very good with R 2 = 0.881 for Lake Łapalickie and 0.929 for Lake Reskowskie.…”
Section: Discussionmentioning
confidence: 86%
“…Such studies usually involve analysing ice cover with the use of satellite images or remote video monitoring data (Murfitt and Duguay 2020;Prabha et al 2020) and then ice models are created using such indirectly collected data sets (Tom et al 2020). There are only a few publications on monitoring lakes that are under hydrological control with the use of benchmark lakes (Barańczuk and Barańczuk 2018;Barańczuk 2019).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The latest literature on the Kashubian Lakeland addresses the issue of modelling ice cover emerging on lakes situated in this region (Barańczuk 2018;Barańczuk and Barańczuk 2018;Barańczuk 2019). However, there is only one detailed publication on the ice regime of Lake Raduńskie Górne (Barańczuk et al 2017) covering such a long data series, and there are no publications addressing other lakes of this district.…”
Section: Introductionmentioning
confidence: 99%